A study of different culture media for pomegranate (Punica granatum L.) pollen - Melgarejo P.; Martínez J.J.; Hernández F. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
We test different culture media and environmental conditions in an attempt to improve our knowledge of the most suitable culture media for studying the germinative capacity of pomegranate pollen. Pollen belonging to the clone ME15, a Mollar type, was used because of its regular and abundant flowering and fruit production. We observed that the incorporation of the nutrients Ca plus2 and B plus3 (0.2 ml per 100 ml) in the medium increased the germination percentage. It was also seen that 1 per cent agar gave better results than 1.5 per cent. High percentages of saccharose (10-20 per cent) did not improve germination, although 1-3 per cent did produce notable differences. Similar improvement was observed in an experiment using 3-5-10 per cent saccharose. We therefore conclude that the optimum saccharose concentration is between 10 and 20 per cent, with levels below 10 per cent producing low levels of pollen germination.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)